The increasing role of the private sector in Asian industrial development - Wilfried Lütkenhorst; Jürgen Reinhardt (Intereconomics, 1993)
In recent years, there has been a powerful trend on the global scene and above all in the Asian region for the private sector in general and private industry in particular to assume a growing, and indeed leading, role in economic and industrial development. This article reviews some recent trends of private investment and privatization policies pursued in selected Asian countries and discusses the implications of private sector-led industrial development for the role of governments and international organizations.
Keywords: 330; Development Strategy